PERAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMODERASI MOTIVASI KERJA DAN KOMITMEN ORGANISASIONALTERHADAP KINERJA GURU - Antimah, Siti; Santosa, Agus Budi (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims to analyze the role of transformational leadership style to moderate work motivation and organizational commitment to the performance of teachers in elementary school teachers in UPTD Education Tembalang Sub-district in Semarang City. This type of research is field research (field research) with quantitative approach. Population in this research is Teacher of ASN of State Elementary School in UPTD Pendidikan Tembalang Sub-district Semarang City which amounts to 225 people. Samples were taken using Purposive random sampling technique, a number of 144 Teachers. Data analysis technique starts from instrument test, normality test, multicolonierity test, heterokedastisity test, model test, hypothesis test, and moderation test. The result of the research showed that work motivation had positive and significant effect on teacher performance, organizational commitment had positive and significant effect on teacher performance, transformational leadership had positive and significant effect on teacher performance, moderate transformational leadership weaken the influence of work motivation on teacher performance, and moderate transformational leadership the influence of organizational commitment with teacher performance. Keywords: Work Motivation, Organizational Commitment, Transformational Leadership and Teacher Performance.